Peran Moderasi Dewan Komisaris Independen terhadap Faktor-Faktor yang Memengaruhi Perataan Laba - Wirawan, Vincent; Ulupui, I Gusti Ketut Agung; Handarini, Dwi (LPPM Universitas Negeri Jakarta, 2022)
This study was conducted with the aim of investigating the moderating role of the board of independent commissioners on the factors affecting income smoothing. The sample was selected based on the criteria set by researcher using purposive sampling method resulting with 21 selected companies from 58 infrastructure companies listed on the Indonesia Stock Exchange (IDX) in 2017 to 2021. This study is using the logistic regression analysis method with SPSS Statistic 25. The results of this study indicate that profitability has an influence on income smoothing practices and the board of independent commissioners are able to weaken the influence of profitability to income smoothing practices. However, leverage and firm size have no effect on the income smoothing practices. While the board of independent commissioners are not able to moderate the effect of leverage to income smoothing practices, but the board of independent commissioners are able strengthens the effect of firm size to income smoothing practices.